Needle-free injection enhancement of beef strip loins with phosphate and salt has potential to improve yield, tenderness, and juiciness but harm texture and flavor - Crow, B.A.; Dikeman, Michael E.; Ray, A.N.; Houser, Terry A.; Grobbel, J.P.; Hollis, Larry C.; Phebus, Randall K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Meat tenderness is the most important palatability attribute affecting consumers’ overall eating experience. Injection enhancement and blade tenderization have long been used to improve this important trait. Injection enhancement has been shown to improve tenderness, juiciness, color stability, and cooking yield, but not all solutions have been adequately evaluated. Thus, there is a need to conduct research on the effectiveness of common enhancement solutions. We published results from an extensive study comparing a solution of phosphate, salt, and rosemary with a solution of calcium lactate and rosemary injected by using traditional needle injection. There were no differences in Warner-Bratzler shear force values between treatments, but trained panelists scored steaks enhanced with calcium lactate and rosemary to be less tender and juicy than steaks enhanced with phosphate, salt, and rosemary. However, steaks enhanced with the phosphate solution had a higher incidence of metallic and salty off-flavors, a darker initial color, and more color deterioration. Because needle-free injection enhancement is relatively similar to traditional needle-injection enhancement with regard to food safety, it should be evaluated for its effects on meat color, instrumental tenderness, sensory traits, and yields. Objectives of this research were to determine the effects of injection method (needlefree vs. needle injection) and solution (calcium lactate vs. phosphate solution) on meat color, instrumental tenderness, sensory traits, pump yield, and cooking loss of beef Longissimus lumborum muscles.
Keywords: Beef; Beef strip loins; Phosphate; Salt; Yield; Tenderness; Warner-Bratzler shear force